2004
DOI: 10.1111/j.1464-5491.2004.01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical inertia in the management of Type 2 diabetes metabolic risk factors

Abstract: Greater initiation and intensification of pharmaceutical therapy, particularly for elevated blood pressure or cholesterol, may represent a specific opportunity to improve metabolic control in Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
107
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 24 publications
6
107
0
1
Order By: Relevance
“…Guideline recommendations on treatment thresholds are changing over time and differ slightly between countries, and there can be differences in the health care system that influence the treatment intervention rates. However, similar low rates have been observed in other recent studies (6,7,18,19).…”
Section: Treatment Statusmentioning
confidence: 45%
“…Guideline recommendations on treatment thresholds are changing over time and differ slightly between countries, and there can be differences in the health care system that influence the treatment intervention rates. However, similar low rates have been observed in other recent studies (6,7,18,19).…”
Section: Treatment Statusmentioning
confidence: 45%
“…6,7 However, many patients experience delays in medication intensification. [8][9][10][11][12][13] Delays in treatment initiation and intensification may be partially due to patient beliefs about their chronic diseases. Prior studies have found that patients hold inaccurate beliefs about diabetes and hypertension, which negatively impact decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…We have designated the latter problem as clinical inertia (20), which may limit control of hypertension (21) and dyslipidemia (22) as well as diabetes (23)(24)(25)(26)(27). At Grady Memorial Hospital in Atlanta, there was more clinical inertia and A1C levels were higher in the general medicine primary care clinic as compared with the diabetes specialty clinic (28).…”
mentioning
confidence: 99%